Membangun Integritas dalam Profesi Pendidik: Etika, Tanggung Jawab, dan Akuntabilitas - Pangaribuan, Tumewa; Harianja, Sri Indriani; Nurjannah, Intan; Rahayani, Fitri; Nurhaliza, Adhwa (Universitas Batanghari Jambi, 2025)
The aim of this research is to explore the role of integrity in the teaching profession and its impact on the quality of education. This research uses the literature study method. The literature study was carried out by conducting a comprehensive and systematic search through academic databases such as PubMed, Google Scholar, and educational journal databases to identify literature that is relevant to integrity in the teaching profession. Keywords used include